2020
DOI: 10.1103/physrevd.101.026016
|View full text |Cite
|
Sign up to set email alerts
|

Towards a quantum Oppenheimer-Snyder model

Abstract: We present a consistent canonical formulation of the flat Oppenheimer-Snyder model, including the Schwarzschild exterior. The switching between comoving and stationary observer is realized by promoting the coordinate transformation between dust proper time and Schwarzschild-Killing time to a canonical one. This leads to two different forms of the Hamiltonian constraint, both (almost) deparameterizable with regard to one of these times. A preliminary quantization of these constraints reveals a consistent pictur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
(81 reference statements)
3
19
1
Order By: Relevance
“…As we have already discussed in Ref. [6], our investigation of a different collapse model in Ref. [7] shows that quantum corrections as seen by the comoving observer will cause the dust cloud to bounce instead of collapsing to a singularity.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…As we have already discussed in Ref. [6], our investigation of a different collapse model in Ref. [7] shows that quantum corrections as seen by the comoving observer will cause the dust cloud to bounce instead of collapsing to a singularity.…”
Section: Introductionsupporting
confidence: 51%
“…In Ref. [6] we have presented a canonical formulation of the OS model, and in particular implemented the comoving and the exterior stationary observers explicitly. In this paper we want to quantize the OS model in this form, leading to two different deparametrized quantum theories, one for each observer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found and discussed this equation and its solutions in Refs. [2,47], where we constructed a quantum Oppenheimer-Snyder model, and also in Ref. [1] where it emerged for a quantum Lemaître-Tolman-Bondi model.…”
Section: A Specific Equation Of Motionmentioning
confidence: 99%
“…In fact, it will be shown that, by setting the constraints for the formation of the SBH in the quantized Oppenheimer and Snyder gravitational collapse, one arrives to quantize the SBH, and this will be a remarkable, important result in the quantum gravity's search. In fact, the Oppenheimer and Snyder gravitational collapse and/or some of its modifications have currently a renovated interest among researchers in gravitation, see for example [18,19,20,21,22,23,24] and references within.…”
Section: A Review Of Rosen's Approachmentioning
confidence: 99%